MEMS sensors for sport engineer applications. Issue 1 (February 2021) - Russo, C; Mocera, F; Som`a, A
Abstract: In this paper it is presented a brief introduction about the Micro ElectroMechanical Systems (MEMS) sensors technology and their application and use in healthcare and sport activity in the literature. In these two fields, our research group's applications will then be analyzed with the support of a numerical tool able to replicate human body behavior performing a sport activity, in particular Nordic Walking and Alpine Skiing. The main goal was to obtain a comparison between the numerical and experimental results, in order to validate of the numerical tool and to better understand the sport gesture. The integrated monitoring systems enable a new interpretation of the sport gesture providing the athletes the maximum freedom of movement and allowing them to better perform in their natural training environment.